Immune activation with peptide assemblies carrying Lewis y tumor‐associated carbohydrate antigen. (10th October 2016) - Yamazaki, Yuji; Watabe, Naoki; Obata, Hiroaki; Hara, Eri; Ohmae, Masashi; Kimura, Shunsaku
Abstract : Molecular assemblies varying morphologies in a wide range from spherical micelle, nanosheet, curved sheet, nanotube and vesicle were prepared and loaded with Lewis y (Le y ) tumor‐associated carbohydrate antigen on the assembly surface. The molecular assemblies were composed of poly(sarcosine) m ‐block ‐poly(L ‐lactic acid)30 ( m  = 15 or 50, Lactosome), poly(sarcosine) m ‐block ‐(D /L ‐Leu‐Aib) n ( m  = 22 or 30, n  = 6 or 8) and their combinations. The molecular assemblies carrying Le y on the surface were administered in BALB/c nu/nu mice. The major epitopes of the molecular assemblies are commonly Le y and poly(sarcosine). IgM productions upon administrations of the molecular assemblies were assayed by ELISA, showing that anti‐poly(sarcosine) IgM was highly produced by Lactosome of spherical micelle but with a negligible amount of anti‐Le y IgM. On the other hand, the nanosheet of the interdigitated monolayer triggered the production of anti‐Le y IgM but with less anti‐poly(sarcosine) IgM production. Taken together, IgM specificity differs according to the molecular environment of the epitopes in the molecular assemblies. The antigenicity of poly(sarcosine) was augmented in polymeric micelle providing loose environment for B cells to penetrate in, whereas a high density of Le y on the molecular assembly was required for anti‐Le y IgM production. The antigenicity of Le y is therefore dependent on the molecular assemblies on which Le y is displayed on the surface. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Peptide assemblies taking various morphologies were prepared with using amphiphilic block polymers having the same hydrophilic poly(sarcosine) block. Nanosheet carrying Lewis y antigen (Le y ) on the surface was found to be the most effective to produce anti‐Le y IgM due to the high density of Le y on the surface. Other peptide assemblies mainly produced anti‐poly(sarcosine) IgM. The results strongly imply that B cells differ in modes to recognize the epitopes in the molecular assemblies.